Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane